PENINGKATAN HASIL BELAJAR IPS SISWA KELAS 4 MELALUI METODE BERMAIN PERAN BERBANTUAN MEDIA KANTIN SEKOLAH - Agus Setiyawan; Slameto . (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract : Increased Student Class IPS Learning Outcomes Through School Playing Role Assisted Methods School Cafeteria. The purpose of this study is to improve the learning outcomes of IPS as well as describe the steps of role learning model with school canteen media in improving the learning outcomes of IPS students grade 3 SDN 02 Genengadal Purwodadi. Subjects of this study amounted to 16 students consisting of 9 male students and 7 female students. Technique of data collecting using test and observation. The data obtained will be analyzed by giving exposure to detail the average increase of learning outcomes from the cognitive, affective and psychomotor aspects of the students to find out the difference in the value of learning outcomes between cycles. The results obtained in this research that is the increase of learning outcomes IPS grade 3 students SDN 02 Genengadal Purwodadi through the implementation of learning model role play with school canteen media. Step by step model of role play with school canteen media can improve student learning result because in student learning divided into 2 group, then teacher ask student in group to discuss and study play role script, after that teacher invite student to school cafeteria to play role And dialogue according to a given script. Keywords : Learning Outcomes, Role Playing Models With School                    Canteen Media Abstrak : Peningkatan Hasil Belajar IPS Siswa Kelas 4 Melalui Metode Bermain Peran Berbantuan Media Kantin Sekolah. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPS serta mendeskripsikan langkah-langkah model pembelajaran bermain peran dengan media kantin sekolah dalam meningkatkan hasil belajar IPS siswa kelas 3 SDN 02 Genengadal Purwodadi. Subyek penelitian ini berjumlah 16 siswa yang terdiri dari 9 siswa laki-laki dan 7 siswa perempuan. Teknik pengumulan data menggunakan tes dan observasi. Data yang didapat akan dianalisis dengan cara memberikan paparan detail kenaikan rata-rata hasil belajar dari ranah kognitif, afektif dan psikomotorik siswa untuk mengetahui selisih peningkatan nilai hasil belajar antar siklus. Hasil yang didapatkan dalam penelitian ini yakni terjadinya peningkatan hasil belajar IPS siswa kelas 3 SDN 02 Genengadal Purwodadi melalui implementasi model pembelajaran bermain peran dengan media kantin sekolah. Langkah-langkah model pembelajaran bermain peran dengan media kantin sekolah dapat meningkatkan hasil belajar siswa karena dalam pembelajaran siswa dibagi menjadi 2 kelompok, kemudian guru meminta siswa dalam kelompok untuk berdiskusi dan mempelajari naskah bermain peran, setelah itu guru mengajak siswa ke kantin sekolah untuk bermain peran dan berdialog sesuai dengan naskah yang telah diberikan. Kata Kunci : Hasil Belajar, Model Pembelajaran Bermain Peran Dengan                     Media Kantin Sekolah